Can insects develop resistance to insect pathogenic fungi? - Ivan M Dubovskiy (Public Library of Science (PLoS), 2013)
Microevolutionary adaptations and mechanisms of fungal pathogen resistance were explored in a melanic population of the Greater wax moth, Galleria mellonella. Under constant selective pressure from the insect pathogenic fungus Beauveria bassiana, 25(th) generation larvae exhibited significantly enhanced resistance, which was specific to this pathogen and not to another insect pathogenic fungus, Metarhizium anisopliae. Defense and stress management strategies of selected (resistant) and non-selected (susceptible) insect lines were compared to uncover mechanisms underpinning resistance, and the possible cost of those survival strategies. We hypothesize that the insects developed a transgenerationally primed resistance to the fungus B. bassiana, a costly trait that was achieved not by compromising life-history traits but rather by prioritizing and re-allocating pathogen-species-specific augmentations to integumental front-line defenses that are most likely to be encountered by invading fungi. Specifically during B. bassiana infection, systemic immune defenses are suppressed in favour of a more limited but targeted repertoire of enhanced responses in the cuticle and epidermis of the integument (e.g. expression of the fungal enzyme inhibitor IMPI, and cuticular phenoloxidase activity). A range of putative stress-management factors (e.g. antioxidants) is also activated during the specific response of selected insects to B. bassiana but not M. anisopliae. This too occurs primarily in the integument, and probably contributes to antifungal defense and/or helps ameliorate the damage inflicted by the fungus or the host's own immune responses.